Correlation of adolescents' self-concept and self-esteem with some unwholesome behavior - Renata Marčič (Psihološka Obzorja, 2007)
The purpose of the study was to investigate the correlations between self-image, self-esteem and some unwholesome behavior (alcohol consumption, cigarette and marihuana smoking, overeating at a meal, television watching and computer use in spare time) in Slovenian adolescents. We used Offer Self-image Questionnaire for adolescents, Rosenberg Self-esteem Scale and Unwholesome behaviour Questionnaire that was made for the purpose of this research. In the research 392 high school students participated, aged around 15 and 18 years, approximately evenly represented by gender and age. Data was attained in class groups. The results showed low, but statistically significant correlations between some self-concept areas and unwholesome behavior. The highest correlations emerged between the sexual attitudes and all unwholesome behavior. Students with more positive sexual self-concept behave unhealthier. Family self, morals and vocational-educational goals were significantly negatively correlated with most of unwholesome behavior, which suggests that individuals with better family, moral and academic self-concept behave healthier. Significant negative correlations emerged also with coping self: individuals with better self-concept in mastery of the external world and superior adjustment behaved healthier. None of the unwholesome behavior correlated with self-esteem. Results are mainly consistent with previous studies, but also contribute to new comprehensions in psychological theory and practice.